ESTUDO DO EFEITO ANTIOXIDANTE DA CASCA DO ALHO (ALLIUM SATIVUM) PARA BIODIESEL DE CANOLA - PELEGRINI, DÉBORA YUMI (2022)
During the decades the planet has suffered several environmental problems due to the use of oil as a raw material in the manufacture of fuel, so the studies related to clean biofuels have increased significantly. Biodiesel has been an alternative to replace fossil fuels, opening a range of production techniques for better quality, innovative alternative routes and the addition of different antioxidants to prevent lipid oxidation of oils. These compounds can be synthetic or natural, both are widely used. However, the synthetic ones can cause harm to the human organism, unlike the natural ones. Tocopherol (vitamin E), present in citric acid, is an example of an antioxidant that is widely used because of its efficiency. Garlic peel is an inedible part and is not consumed, so it fits as agro-industrial waste that contains in its composition polyphenols that present antioxidant activity. The objective of this work is to use the residue of pulverized garlic peel as a natural antioxidant applied to canola oil in biodiesel production. As techniques were used infrared spectroscopy (FTIR) and analysis of elemental composition of garlic peel by EDXRF, accelerated oxidation test (Rancimat® 873), analysis of specific mass, conductivity, pH, viscosity, gas chromatography (GC) in determining the content of esters present in biodiesel and the star experimental planning was 2², cubic model. The extraction media used for this study were: acid, basic and neutral, which were used in the process of obtaining canola biodiesel. The result for canola biodiesel with the addition of 17 g.L-1 with an extraction time of 45 minutes, presented an induction time of 15.46 hours, when we compare this result with the one obtained by pure canola oil that presented a time of 7.95 hours, it is evident the antioxidant capacity of garlic peels. The results obtained for the combination of garlic peel and citric acid at 0.1% was 22 hours, such values meet the minimum required by the ANP of 12 hours.